Impact of Additives on Heterogeneous Crystallization of Acetaminophen - Hsinyun Hsu; Lynne S. Taylor; Michael T. Harris (International Journal of Chemical Engineering)
Introducing foreign substrates or additives is the common way to regulate polymorphism or kinetics of crystallization. Most present studies consider the substrate factor and additive factor separately. Here, the interplay between the additive, crystallizing molecules, and the substrate was investigated. Acetaminophen (APAP) was used as the model compound. 5 wt.% dioctyl sodium sulfosuccinate (AOT), poly(acrylic) acid (PAA), and hydroxypropyl methylcellulose (HPMC) were employed as additives. The interfacial crystal growth rate of APAP in the presence of additives was studied between slides coated with chitosan (CS) film. The crystallization kinetics of the additive/APAP mixture on CS substrate was also investigated. The additive/APAP was characterized by differential scanning calorimetry (DSC), and the interfacial molecular interaction was studied by Fourier transform infrared spectroscopy (FTIR). The results indicate that the additive-substrate interaction can change the interfacial growth behavior observed in the additive-APAP binary system. Nevertheless, crystallizing without confinement, the additive-APAP interaction is more effective at controlling the crystallization of APAP, and the substrates did not have much effect.